Engaging the Public Intimacy of Whiteness: the Indigenous Protest Poetry of Romaine Moreton (Journal of the Association for the Study of Australian Literature, 2008)
In this article I embark upon an investigation of the politico-aesthetics of a trajectory of Australian indigenous poetry which overtly undertakes political and social critique and in doing so foregrounds the relations between colonial history and representation. I investigate whether the category of ‘protest literature’ can do any useful cultural and literary work in talking about this literature. I take the work of Romaine Moreton as exemplary of this tradition and examine how her poetry works rhetorically and performatively on its audience.